Coalescence of fluid particles with deformable interfaces in non-Newtonian media. (November 2021) - Fanebust, Maria; Ozan, Suat Canberk; Jakobsen, Hugo Atle
Abstract: The drainage of the non-Newtonian film between two approaching fluid particles are studied. The non-Newtonian continuous phase is a generalized Newtonian fluid that obeys the power-law model, and the deformable particle interfaces are allowed to have any degree of tangential mobility. The interaction is a gentle collision with a constant relative approach velocity. The film equations are simplified by using the lubrication theory in the thin film limit and combined with the boundary integral method. The effect of the non-Newtonian behavior on the film drainage and on the coalescence time is investigated through the power index. It is found that the non-Newtonian behavior significantly affects the number and type of the rims emerging at the interfaces. At a given approach velocity, when there are no rims or when the interfaces are fully mobile, the coalescence times for Newtonian and non-Newtonian fluids appear to be the same. Otherwise, the coalescence time increases with the power index, i.e., it is faster for shear-thinning fluids and slower for shear-thickening ones. This effect of the non-Newtonian behavior is found to amplify with the tangential mobility of the interfaces and the relative approach velocity. Highlights: Film drainage model for the power-law fluid is derived. Effect of non-Newtonian behavior on drainage is investigated. Coalescence time is given as a function of power index. Impacts of interfacial mobility and approach velocity are examined.